2019
DOI: 10.1007/s10903-019-00861-1
|View full text |Cite
|
Sign up to set email alerts
|

Church-Based Sleep Screenings to Detect Mental Health Problems Among Korean-Americans

Abstract: Purpose Korean-American mental health is poorly understood, and screening for sleep disturbances may be an effective means of identifying at-risk individuals. Design In partnership with a Korean-American church in Los Angeles, an online survey was administered. Setting The study was conducted at a Korean-American church in Los Angeles, California. Subjects The sample consisted of 137 Korean-Americans drawn from the church congregation. Measures Sleep disturbances were measured using a single ordinal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Seven of the studies were conducted mostly in California or New York using primary data collection methods. The methodology employed in the studies varied: six used qualitative approaches, one used literature review [ 40 ] and two used quantitative data analyses [ 41 , 42 ]. A limited number of studies utilized a guiding theoretical framework.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the studies were conducted mostly in California or New York using primary data collection methods. The methodology employed in the studies varied: six used qualitative approaches, one used literature review [ 40 ] and two used quantitative data analyses [ 41 , 42 ]. A limited number of studies utilized a guiding theoretical framework.…”
Section: Resultsmentioning
confidence: 99%
“…4 Other research points to the importance of community-based mental health screening and support groups, such as at temples, churches, and community centers, for AA older adult communities. 5 While our research is unable to establish if wellbeing among AA older adults increased or decreased since the COVID-19 pandemic, it is plausible that the rise in hate crimes targeted toward AA older adults has raised anxiety in the community. There have been a number of community-based initiatives across the United States involving volunteers chaperoning older adult AAs in their neighborhoods, providing safety and companionship.…”
Section: Discussionmentioning
confidence: 84%
“…While improvements in sleep have been associated with positive mental health outcomes (Freeman et al, 2017 ), the lack of significant quantitative and qualitative findings suggest that improvements in sleep may play a lesser role in addressing mental health disparities among Black churchgoers, particularly in comparison to other factors such as social support and sense of community. However, since past research in faith-based settings has observed an important link with sleep outcomes and mental health (Oh et al, 2019 ), further research examining a wider array of sleep indictors (such as sleep quality or disturbances) is warranted.…”
Section: Discussionmentioning
confidence: 99%